(untitled) (Journal of Dhaka Medical College, 2010)
Subarachnoid hemorrhage (SAH) due to rupture aneurysm is a neurologic catastrophe with a very high risk of rebleeding if the aneurysm is not treated. Endovascular coiling has becoming common and has replaced neurosurgical clipping as the treatment of choice. A 48-year-old man came to us with the history of SAH from ruptured cerebral arterial aneurysm and for the first time in the history of Dhaka Medical College Hospital, we had successfully treated by Endovascular coiling. Key words: Subarachnoid haemorrhage (SAH); cerebral DSA; surgical clipping; endovascular coiling. DOI: 10.3329/jdmc.v17i2.6597 J Dhaka Med Coll. 2008; 17(2) : 131-133